2019
DOI: 10.1002/ddr.21514
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant evaluation and docking analysis of VV‐Hemorphin‐5 analogues

Abstract: VV-Hemorphin-5 is an endogenous opioid peptide of the Hemorphin family with affinity at opioid receptors. A series of C-amide analogues have been synthesized, based on the structure of VV-Hemorphin-5, modified at position 1 and 7 by the un/natural amino acids (Aa8-Val-Val-Tyr-Pro-Trp-Thr-Gln-NH 2 and Val-Val-Tyr-Pro-Trp-Thr-Aa1-NH 2 ) using SPPS, Fmoc-chemistry. The peptide derivatives were evaluated for their anticonvulsant activity in three acute seizure tests in male ICR mice, the maximal electroshock (MES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Importantly, not only the position, but also the nature of the incorporated group had an impact on this phenomenon. The obtained data provide the basis for anticipation that the described compounds may be considered as a promising template for future design of the more active analogues, as well as in studies of other models of epilepsy [52,[89][90][91][92][93].…”
Section: Hemorphin Analoguesmentioning
confidence: 92%
See 1 more Smart Citation
“…Importantly, not only the position, but also the nature of the incorporated group had an impact on this phenomenon. The obtained data provide the basis for anticipation that the described compounds may be considered as a promising template for future design of the more active analogues, as well as in studies of other models of epilepsy [52,[89][90][91][92][93].…”
Section: Hemorphin Analoguesmentioning
confidence: 92%
“…It is noteworthy that, when isoleucine or 2-aminoisobutyric acid was added at position 1, a decrease in biological activity has been observed. Incorporation of Orn (2,5-diaminopentanoic acid) at Gln position of VV-hemorphin-5 and Dab (2,5-diaminobutanoic acid) moiety at Gln position of VV-hemorphin-7 peptide, respectively led to the analogues posessing good efficacy against the three seizure models [52,[89][90][91][92].…”
Section: Hemorphin Analoguesmentioning
confidence: 99%
“…(5 mL per ventricle) at doses of 0.25, 0.5 and 1 mg, respectively, by means of 28-gauge stainless steel needles attached to 10 mL Hamilton s syringes as described in previous studies. 49,50 The antiseizure effect was evaluated 10 min following the treatment. The doses were chosen based on our previous studies.…”
Section: Voltamperometric Analysismentioning
confidence: 99%
“…39 Based on our previous studies, we showed that hemorphins and their analogues, containing non-proteinogenic and/or natural amino acids, from the N-or C-terminus of the molecules demonstrated dose-and phase-dependent anticonvulsant activity and a lack of neurotoxicity in the rotarod test. [47][48][49][50][51] Our group is one of the leading pioneers in the exploration of anticonvulsant activity of these perspective biopeptides. [47][48][49][50][51] As a natural extension of our research in the synthesis and characterization of new hemorphin analogues as potential anticonvulsants and because of all the above mentioned, herein we illustrated the potential of new N-modified hybrid analogue hemorphins containing a C-5 substituted hydantoin residue as anticonvulsants and inhibitors of sodium channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation